A comparative study of hard/soft PZT-based ceramic composites. Issue 7 (15th May 2016) - Horchidan, N.; Ciomaga, C.E.; Frunza, R.C.; Capiani, C.; Galassi, C.; Mitoseriu, L.
Abstract: The objective of present study is an investigation of the role of mixing level (from macro- to microscale) on the dielectric and ferroelectric properties of doped lead zirconium titanate (PZT) composites with soft/hard counterparts. The composites were prepared by two types of doped PZT (soft and hard), which were mixed on a macroscopic (chessboard) and a microscopic level and densified using a classical sintering procedure. A combined scanning electron microscopy, and atomic force microscopy were performed to obtain new insights about microstructure modifications of the investigated ceramic composites. The dielectric properties and high field and ferroelectric properties demonstrated that the soft behavior is prevailing when using macro-scale mixing, while the micro-scale mixing favors the hard behavior. Therefore, the dominant (soft or hard) behavior can be modified by using different scale mixing methods, providing a possible method of controlling the functional characteristics of PZT-based composites.